229. CARBON-13 BREATH TEST AS AN INVESTIGATIVE TOOL FOR DELAYED CONDUIT EMPTYING AFTER AN OESOPHAGECTOMY. (24th September 2022) - Tham, Ji Chung; Alcocer, Bruno; Forbes, Rosie; Ariyarathenam, Arun; Humphreys, Lee; Berrisford, Richard; Wheatley, Tim; Chan, David; Lewis, Stephen; Sanders, Grant
Abstract: The gold standard for diagnosing delayed conduit emptying (DCE) after an oesophagectomy is with scintigraphy. Current practice of using chest radiographs (CXR) and nasogastric tube (NG) output to diagnose DCE is useful clinically but is not as accurate as scintigraphy. A radiation-free procedure with higher accuracy that can be easily carried out at the bedside is needed. We proposal that the carbon-13 breath test is a viable option. Oesophagectomy patients without pyloroplasty were recruited prospectively from 05/12/2017 to 31/12/2019 at a single centre. Age, gender, BMI, ASA grade, smoking status, and conduit size were used. DCE was diagnosed using parameters determined from CXRs and NG output described previously (1). At day 4/5/6, patients were fasted 6 hours prior to consumption of 100 mL of 193 kcal ice-cream laced with carbon-13 octanoic acid. Breath was captured at times 0, then every 30 minutes up to 4 hours and analysed using a gas spectrometer. Carbon-13 half-life excretion (t½) and estimated maximum excretion (tmax) was calculated using the formulas by Ghoos et al (2). There were 65 patients with 24 DCE patients. Apart from gender (p = 0.015), there were no differences in demographics between DCE and non-DCE patients. Differences were seen in both t½ and tmax. T½ was 3.04 hours [95%CI (2.91, 3.52)], and 3.54 hours [95%CI (3.41, 5.39)] in non-DCE, and DCE patients, respectively (p = 0.034). At time points 30, 60 and 90-minutes, Carbon-13 excretion were different, with p = 0.04, 0.015, and 0.034, respectively. Tmax was 1.68 hours [95%CI (1.45, 2.04)], and 2.15 hours [95%CI (1.98, 3.24)] in non-DCE, and DCE patients, respectively (p = 0.011). This study has shown that the carbon-13 breath test is a viable tool to diagnose DCE. Further analysis and comparison with scintigraphy is required to validate the test. Although a gas spectrometer was used in this study to analyse patients' breath, bedside testing devices are currently available and should be used in future studies.